Pengaruh Kualitas Produk dan Kualitas Layanan terhadap Tingkat Kepuasan Konsumen dan Dampaknya Terhadap Loyalitas Pelanggan (Studi Empiris pada Pizza Hut Duta Pertiwi Mall Semarang) - Cefiro, 08.05.51.0141 Roval Allenby; Yulianto, Heru (Students Journal of Economic and Management, 2012)
Todays the businessâs competition is becoming intense. Including competition in food business. Pizza Hut is a services company specializing in food and baverages are very high regard of quality service and products. This research aims to find out whether the product quality and service quality of positive influential to consumerâs satisfaction and customer satisfaction influential favorably to loyality. Therefore this research took the title âInfluence of Product Quality and Service Quality Toward Customer Satisfaction and Its Impact on Customer Loyalty (Empirical Study At Pizza Hut Duta Pertiwi Mall)